The Purity of Alcohol from the Viewpoint of Shiite Jurisprudence - A Nikzad (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Considering various applications of alcohol in human life in today s world, it is important to discuss whether alcohol is pure (Tahir) or impure (Najis). The present study was conducted to investigate its jurisprudential aspects from the viewpoint of Shiite Islam (one of the two main branches of Islam). METHODS: This study was designed based on library collection development method as well as methods of reasoning by reviewing texts published on purity (Taharat) and impurity (Najasat) of alcohol and any intoxicating liquor. Qur anic verses, formal legal opinions of religious scholars (Fatwas) and narrations (Hadiths= Record of the traditions or sayings of the Prophet Muhammad) were used here. FINDINGS: There is disagreement between the jurists (Faqīhs) about the purity of alcohol. The argument of the jurists who believe in the impurity of alcohol is based on the fact that alcohol is an intoxicating liquor and that anything that is intoxicating is impure, and as a result alcohol is impure. In this study, both introductions of this argumentation are questioned by a careful examination of the narrations (Hadiths) and arguments (Dalil). That is, the arguments for the impurity of any intoxicating liquor has been criticized and if we assume that any intoxicating liquor is impure, it has been proved that alcohol is not considered an intoxicating factor. CONCLUSION: The results of this study show that there is no reason for the impurity of alcohol, and we can rely on the formal legal opinions of religious scholars (Fatwas) about the purity or impurity of alcohol based on the principle of purity (Everything is purie until its impurity is proved).